POSTPRANDIAL GLYCEMIC RESPONSES OF YOUNG HEALTHY WOMEN TO VARIED MACRONUTRIENT COMPOSITION AND PROTEIN SOURCES IN BREAKFASTS MEALS - Dr. Fazia Ghaffar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND: Breakfast is considered to be the most important meal of the day and a healthy breakfast can help reduce the burden of many life style diseases. An increasing number of adolescent and young females are prone towards skipping breakfasts or are consuming unhealthy breakfasts which demand improved dietary strategies. OBJECTIVES: The objectives of the current study were to design plant-based economical and locally available foods in breakfast meals and then compare their nutritional composition, sensorial properties. satiety and postprandial glycemic regulation among young healthy females. METHODS: The study analyzed the proximate composition, mineral composition, and overall acceptability of two conventional, one reference, and six diversified breakfast meals. One control, a reference, and three diversified breakfasts meals were studied for postprandial glycemic responses in comparison with” no breakfast”. Blood glucose was tested at fasting, 30, 60, 120, 180, and 240 minutes respectively. Satiety/hunger perception was assessed throughout the study period. RESULTS: A good number of students missed breakfast on most week days (62%). With the addition of meat, egg, mung beans, chickpea flour, and ground peanuts the mean mineral content, percent protein and percent fiber increased significantly while percent fat remained same except the one that contained peanut stuffed bread. The perceived sensory attributes of the experimental breakfasts in comparison with the conventional and reference breakfasts were higher. Glycemic responses showed stability with the addition of proteins (irrespective of their source protein). The diversified breakfasts were reported to be effective in the stability of satiety against no breakfast. CONCLUSION: The study concludes that the addition of protein, plant or animal, and maintaining the overall energy nutrients balance to breakfast better regulate glycemic responses.